Kompetensi Manajerial Kepala Sekolah dalam Perencanaan Peningkatan Mutu Pendidikan di SMK Negeri Kota Samarinda - Harliansyah, Harliansyah; Hanim, Zaenab; Azainil, Azainil (Attractive : Innovative Education Journal, 2022)
This study analyzed the managerial competence of the principal in planning, implementing, monitoring, and the obstacles to improving the quality of education at SMK Negeri Samarinda. It was qualitative approach with case study method. The results showed that (1) the principal managerial competence in planning for improving the quality of education was the ability to prepare annual budget work plans and implementation of school work programs, the ability to collaborate, create a good and innovative climate and culture, human resource activities, student learning outcomes. and the use of technology, especially in the fields of curriculum, student affairs, staffing, educational facilities, school administration, finance, and community relations, (2) implementation of principal managerial competence in accordance with quality improvement planning was that the principal conducts school organizing, resource empowerment, school management, empowering teachers and staff, facilities and infrastructure, students, curriculum, school finance, monitoring, evaluation, and reporting, (3) managerial competence of school principals in carrying out supervision of improving the quality of education was carried out properly through monitoring activities and evaluation every semester, carried out together with the school's internal quality assurance team and involving staff, teachers, and education personnel, (4) obstacles faced by school principals in planning for improving the quality of education are financial limitations, discipline, and infrastructure. Keywords: Managerial Competence, Increasing Education Quality, Planning Education Quality